Estrategias de enseñanza aprendizaje en contabilidad y su incidencia en el rendimiento académico de los estudiantes del tercero de bachillerato técnico de la Unidad Educativa Nicolás Infante Díaz cantón Quevedo provincia de los Ríos - Veas Mendoza, Soraida Cristina (2018)
The present project faith with the aim of applying teaching strategies that influence the learning process in the accounting. The current world demands competitiveness, efficiency in each of the operations that are going to be carried out, that is why the academic preparation that is carried out must be innovated in accordance with the required standards, forming dynamic capable professionals with outstanding academic and professional rests. in each field in which they are made. In view of the above, the main objective of this project is to determine the incidence of the application of innovative learning strategies in the teaching of this area, providing a pedagogical option that helps teachers achieve meaningful, permanent learning in an environment participatory and dynamic. The implementation of a didactic guide with teaching strategies for the area of accounting of the third year students of baccalaureate, seeks to improve the teaching procedures in the Educational Unit at the same time to help fulfill its mission that is to provide a technical education with solid values, that make young people, professional leaders capable of facing the reality of the working world, in the scientific, technical and technological fields with quality and excellence